Pengaruh Norma Subjektif dan Risiko Terhadap Minat Penggunaan Byond by BSI Melalui Pengetahuan Prinsip Mashlahah - Cholilah, Aprilinda Ummi; Sopingi, Imam (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Digital technology in the banking sector continues to develop, marked by the presence of services such as Byond by BSI. Hasyim Asy'ari University has collaborated with Bank Syariah Indonesia in paying UKT through virtual accounts. However, most students have not used the Byond by BSI application as their main means of payment. This study aims to explore the impact of subjective norms and risks on students' interest in using the Byond by BSI application, with an understanding of the mashlahah principle as a mediating factor. The research method applied uses a quantitative approach through a survey of 102 active UNHASY students from the 2021–2024 intake, who were selected using the purposive sampling method. Data were obtained through questionnaires and analyzed using outer and inner model testing with PLS 3 software. The results showed that subjective norms and knowledge of the mashlahah principle influenced the interest in using Byond by BSI, while risk did not have a direct effect. However, knowledge of the mashlahah principle was proven to mediate the influence of subjective norms and risks on interest in use. These findings indicate that understanding the mashlahah principle can strengthen social influence and reduce the impact of risk, thereby increasing the use of Byond by BSI.